Effect of Independent Outside Directors and Board Size on Earnings Management in Saudi Family Businesses - Madhawi Alknani; Hashem Alshurafat; Nafisah Yami; Maha Shehadeh (Ianna Journal of Interdisciplinary Studies)
Background: The Board of Directors (BOD) has greater authority in a firm and is responsible for protecting investors from manipulation and monitoring companies. Few studies have analysed this relationship in family businesses.